Um ambiente computacional para o processo de prospectiva estratégica auxiliado por grandes modelos de linguagem - Neres, Alan Felipe de Lima (2025)
Future studies play a crucial role in business, political, and social contexts, involving various methods, techniques, and tools. Although some tools support the work of foresight practition- ers, there is still a lack of computational solutions to organize and systematize this process. This study proposes a computational environment to support the foresight process, leveraging Soft- ware Engineering principles and the capabilities of Large Language Models (LLMs). As a re- sult, this work presents the design of a computational application developed to support the nine stages of the foresight process, as structured by Godet and Durance. This application will be based on a flexible and extensible architecture, allowing future evolution with the incorporation of new functionalities. Instead of integrating existing tools, the focus is on creating a computa- tional environment designed to systematically structure and support foresight practice.